PP.21.31: COMPARISON OF THE EFFECTS OF TWO DIFFERENT ANTIHYPERTENSIVE DRUG COMBINATIONS ON ARTERIAL DISTENSIBILITY AND PULSE WAVE VELOCITY IN ELDERLY PATIENTS WITH ISOLATED SYSTOLIC HYPERTENSION. (June 2015) - Cairo, M.; Van Bortel, L.M.; Seravalle, G.; Maloberti, A.; Makel, W.; Fici, F.; Mancia, G.; Grassi, G.
Abstract : Objective: Isolated systolic hypertension (ISH) is a major risk factor for cardiovascular disease and results primarily from elastic artery stiffening. Whether and to what extent the vascular abnormalities decribed in ISH can be affected by antihypertensive combination drug therapy is still debated Design and method: 24 ISH patients, aged > 65yrs recruited in the randomised, double blind, parallel group NEHIS study were randomized in a double blind fashion to Nebivolol 5 mg/Hydrochlorothiazide 12.5 mg (NH, n = 12) or Irbesartan 150 mg/Hydrochlorothiazide 12.5 (IH, N = 12) once daily for a 12 week period. Measurements included, along with clinic and ambulatory blood pressure (BP), carotid and femoral arterial pulse waves (VP-2000 Omron Healthcare) allowing to obtain an index of arterial stiffness, i.e. pulse wave velocity. Other vascular indices included carotid and femoral artery distensibility coefficient as well compliance coefficient. Results: NH and IH induced similar significant (p < 0.01) reduction in ambulatory SBP and DBP values, which were coupled in the case of NH with a slightly greater, although not significant, office SBP decrease. IH caused a slight, not significant, increase in carotid distensibility coefficient (from 0.011 ± 0.003 to 0.015 ± 0.04 10-3 mmHg-1, P = NS) and in carotid compliance coefficient (from 0.091 ± 0.023 to 0.123 ± 0.026 mm2/kPa, mean ± SD, P = NS). Similar results were obtained by NH (distensibility 0.008 ± 0.002 to 0.010 ± 0.004 10-3 mmHg-1, P = NS, compliance 0.091 ± 0.02 to 0.123 ± 0.02 mm2/kPa, P = NS). Similar effects were also seen for femoral artery distensibility and compliance. Pulse wave velocity was only slightly and not significantly reduced by combination drug treatment both in the NH (from 13.6 ± 3.o to 11.5 ± 2.7 cm/sec) and in IH (from 16.9 ± 4.4 to 15.6 ± 3.7 cm/sec) group (P = NS). Conclusions: These data provide evidence that in ISH the vascular functional alterations are not reversed by two different drug treatments capable to exert similar antihypertensive effects. Because nebivolol and irbesartan, alone or in combination treatment, have been shown in systodiastolic hypertension to improve arterial distensibility and compliance, well as arterial stiffness, these findings may suggest that the vascular alterations observed in ISH are not reversible, at least in the short-term period, even by a combination drug treatment capable to effectively reduce elevated BP values.